2008
DOI: 10.3945/jn.108.096404
|View full text |Cite
|
Sign up to set email alerts
|

A 19-Base Pair Deletion Polymorphism in Dihydrofolate Reductase Is Associated with Increased Unmetabolized Folic Acid in Plasma and Decreased Red Blood Cell Folate

Abstract: Dihydrofolate reductase (DHFR) catalyzes the reduction of folic acid to tetrahydrofolate (THF). A 19-bp noncoding deletion allele maps to intron 1, beginning 60 bases from the splice donor site, and has been implicated in neural tube defects and cancer, presumably by influencing folate metabolism. The functional impact of this polymorphism has not yet been demonstrated. The objective of this research was to determine the effects of the DHFR mutation with respect to folate status and assess influence of folic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 40 publications
4
70
2
Order By: Relevance
“…The DHFR in human liver-cell homogenates shows a wide range of activity between individual samples [3], suggesting large differences in an individual's ability to reduce FA. A limited ability of the mutated enzyme to reduce FA (at high FA intake ≥ 500 μg/day) caused higher unmetabolized FA in blood [62]. The mutated enzyme (del/del) was associated with lower whole blood folate in individuals receiving < 250 μg/day FA [62].…”
Section: Genetic Polymorphisms Affect Folate Bioavailability Utilizamentioning
confidence: 99%
See 1 more Smart Citation
“…The DHFR in human liver-cell homogenates shows a wide range of activity between individual samples [3], suggesting large differences in an individual's ability to reduce FA. A limited ability of the mutated enzyme to reduce FA (at high FA intake ≥ 500 μg/day) caused higher unmetabolized FA in blood [62]. The mutated enzyme (del/del) was associated with lower whole blood folate in individuals receiving < 250 μg/day FA [62].…”
Section: Genetic Polymorphisms Affect Folate Bioavailability Utilizamentioning
confidence: 99%
“…A limited ability of the mutated enzyme to reduce FA (at high FA intake ≥ 500 μg/day) caused higher unmetabolized FA in blood [62]. The mutated enzyme (del/del) was associated with lower whole blood folate in individuals receiving < 250 μg/day FA [62]. The effects of the genotype on plasma or RBC folate or tHcy are currently controversial [42,109].…”
Section: Genetic Polymorphisms Affect Folate Bioavailability Utilizamentioning
confidence: 99%
“…Both the DHFR 19-bp deletion and SHMT C1420T polymorphisms involved in folate/Hcy metabolism have been associated with variations in the concentrations of Hcy and folate in several populations (Heil et al, 2001;Chen et al, 2004;Lim et al, 2005;Gellekink et al, 2007;Kalmbach et al, 2008;Stanisiawska-Sachadyn et al, 2008;Mendes et al, 2010;Marucci et al, 2012). Thus, the aim of the present study was to investigate the association between the DHFR 19-bp deletion and SHMT C1420T polymorphisms and the serum folate and plasma Hcy and methylmalonic acid (MMA) concentrations in individuals with DS.…”
mentioning
confidence: 97%
“…A 19-base pair (bp) deletion polymorphism in intron-1 of the Dihydrofolate reductase (DHFR) gene, located on chromosome 5q11.2, has been identified ( Johnson et al, 2004) and Kalmbach et al (2008) demonstrated that this is a functional polymorphism. Study shows that the 19-bp deletion polymorphism is associated with increased expression of the DHFR gene, responsible for the conversion of dihydrofolate in tetrahydrofolate (THF) (Xu et al, 2007), and changes of folate/ Hcy metabolism (Gellekink et al, 2007;Kalmbach et al, 2008;Stanisiawska-Sachadyn et al, 2008;Mendes et al, 2010).…”
mentioning
confidence: 99%
“…Folate deficiency can reduce global DNA methylation, which is associated with genetic instability and the formation of tumors [12]. Low folate intake has been positively associated with the occurrence of colon [12], breast [17,18,19,20], lung [17,18,21,22], colorectal [17,18,21,22], and head and neck cancer [23]. The presence of C776G polymorphism of the TC2 gene in transcobalamin leads to substitution of the amino acid proline arginine at codon 259 (P259R) [24,25].…”
Section: Introductionmentioning
confidence: 99%